Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual Dan Kecerdasan Spiritual Auditor Terhadap Kualitas Audit - Panji Sentika; Liza Laila Nurwulan (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2023)
This study aims to determine the magnitude of the influence of emotional intelligence, intellectual intelligence and spiritual intelligence on audit quality at 10 Public Accounting Firms in Bandung City registered with the Indonesian Institute of Certified Public Accountants (IAPI) emotional intelligence, intellectual intelligence and spiritual intelligence as independent variables, audit quality as the dependent variable. The research approach used in this research is descriptive analysis and verification using primary data. The sampling technique used is purposive sampling. From the established criteria, the number of samples taken is 53 auditors. Statistical analysis used in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, t test and f test. Based on the results of research conducted, it can be seen that there is a reciprocal relationship between emotional intelligence and intellectual intelligence of 69.3%, emotional intelligence with spiritual intelligence of 60.5% and intellectual intelligence with spiritual intelligence of 74.2% partially emotional intelligence has a significant effect on audit quality with a contribution of 30.1% intellectual intelligence has a significant effect on audit quality with a contribution of 27.1%. spiritual intelligence has a significant effect on audit quality with a contribution of 30.5% emotional intelligence, intellectual intelligence and spiritual intelligence have a positive effect simultaneously giving an influence of 87.7%. This shows that the better emotional intelligence, intellectual intelligence and spiritual intelligence, the higher the quality of the audit results.